2011
DOI: 10.1002/jssc.201100554
|View full text |Cite
|
Sign up to set email alerts
|

Separation and purification of isorhamnetin 3‐sulphate from Flaveria bidentis (L.) Kuntze by counter‐current chromatography comparing two kinds of solvent systems

Abstract: The first preparative separation of a flavonoid sulphate isorhamnetin 3-sulphate from Flaveria bidentis (L.) Kuntze by counter-current chromatography (CCC) was presented. Two kinds of solvent systems were used. A conventional organic/aqueous solvent system n-butanol-ethyl acetate-water (4:1:5, v/v) was used, yielding isorhamnetin 3-sulphate 2.0 mg with a purity of 93.4% from 83 mg of pre-enriched crude extract obtained from 553 mg ethanol extract by macroporous resin. A one-component organic/salt-containing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The leaves of H. portulacoides have high average levels of sulfated flavonoids (Vilela et al 2014), therefore being a potential source of these compounds of pharmacological interest (Correia-da-Silva et al 2014). For instance, Flaveria bidentis (L.) Kuntze is recognized as a good source of sulfated flavonoids, namely isorhamnetin 3-sulfate, with about 744 mg kg −1 DM (Xie et al 2012), only 1/4 of the content exhibited by H. portulacoides. Moreover, long chain chloroalkanes were also recorded in leaf waxes (Grossi & Raphel 2003) and volatile organic compounds in root exudates (Oliveira et al 2012).…”
Section: The Potential Of Halimione Portulacoidesmentioning
confidence: 99%
“…The leaves of H. portulacoides have high average levels of sulfated flavonoids (Vilela et al 2014), therefore being a potential source of these compounds of pharmacological interest (Correia-da-Silva et al 2014). For instance, Flaveria bidentis (L.) Kuntze is recognized as a good source of sulfated flavonoids, namely isorhamnetin 3-sulfate, with about 744 mg kg −1 DM (Xie et al 2012), only 1/4 of the content exhibited by H. portulacoides. Moreover, long chain chloroalkanes were also recorded in leaf waxes (Grossi & Raphel 2003) and volatile organic compounds in root exudates (Oliveira et al 2012).…”
Section: The Potential Of Halimione Portulacoidesmentioning
confidence: 99%
“…2 Previous studies showed that avonoids are the main secondary metabolites in invasive weeds and possess various biological activities. [2][3][4][5] Detection and identication of the useful avonoid components in invasive weeds are an essential step to take advantage of invasive weeds.…”
Section: Introductionmentioning
confidence: 99%
“…The prominent advantage of this strategy is the complete non-target or semi-target identication. Using this approach, we have successfully characterized the avonoid components including the avonoids using manual analysis by HSCCC, HPLC, ESI-MS, 1 H NMR and 13 C NMR analysis 2,5,21 in the invasive weed Flaveria bidentis (L.) Kuntze (F. bidentis). The present approach is reliable and applicable to the identication of non-target avonoids in invasive weeds.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of monoterpenes was usually using conventional methods such as silica and/or gel column chromatography , which were energy exhausting, tedious, time consuming, and had low efficiency. In recent years, high‐speed counter‐current chromatography (HSCCC), which can eliminate irreversible absorptive loss of samples and offers high resolution comparable to column chromatography, has been widely used in fast separation and purification of chemical components from Chinese medicinal herbs . Further, elution–extrusion counter‐current chromatography (EECCC), which combines normal elution and extrusion in a single run, was developed by Berthod .…”
Section: Introductionmentioning
confidence: 99%